Was that slip and fall for real? [video surveillance and VideoSave]. - Rosenblatt, A.
Describes the video surveillance system built by VideoSave and the storage of images using compression.
Keywords: Internet access; MPEG-4 system; VideoSave system; Digital image; Image compression; Image recording; Insurance companies; Surveillance system; Surveillance video cameras